First Principles Study of the Interaction of Rare Gases in a U@C60 Fullerene. Issue 18 (7th November 2016) - Lei, Yanyu; Jiang, Wanrun; Gao, Yang; Xu, Dexuan; Wang, Bo; Wang, Zhigang
Abstract: To understand the interaction between rare gases and actinide endohedral metallofullerenes (EMFs), we use first‐principles density functional theory calculations to analyze the UNg@C60 system encapsulating a heavy rare gas atom (Ng=Ne, Ar) in EMF U@C60 . The results show that U and rare gase atoms lose electrons, while the carbon cage gain electrons, and the order of magnitude of charge transfer is about 0.1 e. With the increase of atomic number of rare gases, the polarization effect and electronic correlation between U@C60 and rare gases are gradually enhanced which results in the electron cloud overlap. Our work helps to form a deeper understanding of the embedment mechanism of rare gas in confined conditions. Abstract : Electronic density analysis highlights the weak interaction between rare gases and the U atom in UNg@C60 (Ng=Ne, Ar).